Drug delivery nanoplatform for orthopaedic-associated infections. (2017) - Tsiapla, A.R.; Karagkiozaki, V.; Pappa, F.; Bakola, V.; Choli-Papadopoulou, Th.; Moutsios, I.; Pavlidou, E.; Laskarakis, A.; Logothetidis, S.
Abstract: The number of patients in need of orthopaedic implants has increased rapidly over the past few years. Implant associated infections that are created after an invasive orthopaedic surgery are one of the major causes of implant failure. In this work, a drug delivery nano platform system was fabricated, consisted of Polycaprolactone (PCL) scaffolds loaded with the antibiotic drug vancomycin via Electrospinning process. Titanium implants' surface has been modified with non-woven fibrous coatings while the efficacy and toxicity on fibroblasts were investigated in vitro. Atomic Force Microscopy (AFM) and Scanning Electron Microscopy (SEM) measurements showed the successful fabrication of those structures. Cytotoxicity studies took place in order to examine the cytocompatibilty of the nanoplatform. MTT assay and methylene blue staining showed an excellent cell adhesion and proliferation, thus enhance the cytocompatible behavior in vitro. Drug release kinetics further took place in line with degradation studies in order to evaluate the mass loss of polymers. This drug delivery nano platform is a promising nanovehicle to prevent and treat orthopedic implant-associated infections along with a simultaneously release of the drug in a controllable and sustainable manner.